1975
DOI: 10.1172/jci108090
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum thyroglobulin. A marker of metastases in differentiated thyroid carcinomas.

Abstract: A B S T R A C T The presence of human thyroglobulin (HTg) in serum of patients with differentiated thyroid carcinoma was studied. The thyroglobulin detected in the serum of such patients was identical by immunological criteria to the serum standard used in the radioimmunoassay. The serum thyroglobulin levels in untreated patients with differentiated thyroid carcinoma ranged from 22.0 to 445.0 ng/ml with a mean of 144.3± 46.5 ng/ml (SEM) (n = 10). The mean serum thyroglobulin measured postoperatively in seven o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
1
5

Year Published

1977
1977
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(87 citation statements)
references
References 12 publications
4
77
1
5
Order By: Relevance
“…Its concentration in serum rises with thyroid gland hypersecretion and particularly with thyroid gland damage as after surgery or in subacute thyroidities. The level of serum TG may be very high in some cases of metastatic thyroid carcinoma (Van Herle et al, 1973;Van Herle & Uller, 1975).…”
Section: Circulating Iodinated Compoundsmentioning
confidence: 99%
“…Its concentration in serum rises with thyroid gland hypersecretion and particularly with thyroid gland damage as after surgery or in subacute thyroidities. The level of serum TG may be very high in some cases of metastatic thyroid carcinoma (Van Herle et al, 1973;Van Herle & Uller, 1975).…”
Section: Circulating Iodinated Compoundsmentioning
confidence: 99%
“…Several previous studies (Van Herle et al, 1973 ;Izumi and Larsen, 1978 ;Gardner et al, 1979;Pacini et al, 1980) have demonstrated varying degrees of elevated levels of serum Tg in thyroid diseases such as Graves' disease and subacute thyroiditis. In patients with thyroid carcinoma, Tg is a useful marker for their follow-up (Van Herle and Uller, 1975 ;Pacini et al, 1980), since the levels of serum Tg after thyroidectomy are low or undetectable in patients with complete remission, whereas elevated serum Tg indicates metastasis and/or recurrence of carcinoma.…”
mentioning
confidence: 99%
“…Some of them examined factors which affect the level of serum Tg [14][15][16][17], and others investigated the diagnostic value of the test in the management of thyroid nodules [18][19][20][21][22]. Experts reported that the measurement of serum Tg is of no value in the differential diagnosis of thyroid tumor [8][9][10], but we should be critical of their findings in two respects; an analysis and a study population.…”
Section: Discussionmentioning
confidence: 99%